Associaton between violence and drug consumption with suicide in lesbians, gays, bisexuals, transvestites, and transsexuals: cross-sectional study - Grayce Alencar Albuquerque (Salud Mental, 2018)
Introduction: Lesbian, gay, bisexual, transvestite, and transgender (LGBT) people are affected by prejudice and psychological, physical, and/or sexual violence due to their sexual orientation.Objective: To analyze the association between violence, drug use, and suicide in LGBT people.Method: We interviewed 316 LGBT people from two cities of the Brazilian Northeast by means of a structured instrument. This included questions about sociodemographic data, sexual orientation, type of violence, type and quantity of drugs consumed, and suicide.Results: There was a positive association between physical violence and anabolic consumption (p = .001) and tranquilizers (p = .012). In relation to psychological and verbal violence, there was a positive association with the use of tranquilizers (p = .021) and negative with the use of amphetamines (p = .027). Suicide attempts were associated with having experienced physical (p = .03) and sexual (p = .037) violence. Drug use, especially ecstasy, cocaine, marijuana, and tranquilizers, was also associated with suicide attempts (p = .002, p = .031, p < .001, p < .001, respectively). The participants who had already attempted suicide were more vulnerable to experience violence and consume drugs within 30 days prior to the interview (p < .001).Discussion and conclusion: Psychological/verbal violence showed to be associated with the use of amphetamines, while physical violence was associated with a higher consumption of tranquilizers and anabolic steroids. Suicide attempts were more common among participants who had suffered physical violence and who were users of substances such as ecstasy, cocaine, marijuana, and tranquilizers.